2013
DOI: 10.1073/pnas.1220603110
|View full text |Cite
|
Sign up to set email alerts
|

Hippo-Foxa2 signaling pathway plays a role in peripheral lung maturation and surfactant homeostasis

Abstract: Respiratory distress syndrome (RDS), which is induced by insufficient production of surfactant, is the leading cause of mortality in preterm babies. Although several transcription factors are known to be involved in surfactant protein expression, the molecular mechanisms and signaling pathways upstream of these transcription factors have remained elusive. Here, using mammalian Hippo kinases (Mst1/2, mammalian sterile 20-like kinase 1/2) conditional knockout mice, we demonstrate that Mst1/2 kinases are critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 32 publications
5
66
0
Order By: Relevance
“…These mice died at various time points after birth; most of them perished before they reached 3 weeks of age although a few survived beyond that (Fig, 1I, J, K). These findings are largely similar to reports on Mst1 f/f ; Mst2 −/− mice that also carry Nkx2.1-Cre (Chung et al, 2013). In that study, a conditional allele of Mst1 ( Mst1 f ) (Katagiri et al, 2009) and a null allele of Mst2 ( Mst2 − ) (Oh et al, 2009) were utilized to assess the functional consequence of Mst1/2 removal in the lung.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These mice died at various time points after birth; most of them perished before they reached 3 weeks of age although a few survived beyond that (Fig, 1I, J, K). These findings are largely similar to reports on Mst1 f/f ; Mst2 −/− mice that also carry Nkx2.1-Cre (Chung et al, 2013). In that study, a conditional allele of Mst1 ( Mst1 f ) (Katagiri et al, 2009) and a null allele of Mst2 ( Mst2 − ) (Oh et al, 2009) were utilized to assess the functional consequence of Mst1/2 removal in the lung.…”
Section: Resultssupporting
confidence: 90%
“…Consistent with the expected difference in Cre activity, MST2 protein reduction is more complete and upregulation of YAP targets more pronounced in lungs in which Mst1/2 are removed by Shh-Cre than those induced by Nkx2.1-Cre in our investigation. Of note, a recent study (Chung et al, 2013) reported reduced YAP, CTGF and FOXA2 protein levels in lungs derived from Mst1 f/f ; Mst2 −/− mice that carry Nkx2.1-Cre . It is unclear how this discrepancy has arisen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lung development failure causing reduced airspaces in mutant lungs leaded to mice neonatal death and the mutant mice showed a phenotype mimicking RDS in preterm infants. One study demonstrated Mst1/2 regulated lung development through Foxa2 independently of Yap/Taz signaling (12). However, the other studies indicated that Hippo components Mst1/2 and Mob1 regulated lung development through Hippo effector Yap/Taz, which means a canonical Hippo-Yap signaling pathway was involved (13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…These genetic studies will complement cell-based assays in delineating the interactions of Hippo pathway components in the respiratory system. Interestingly, even though complete deletion of Sav1 in mice leads to embryonic lethality, lungspecific Sav1 knockout mice are viable and fertile without apparent gross abnormalities (12).…”
Section: Discussionmentioning
confidence: 99%